Propuesta de intervención para mitigar el impacto psicológico a causa de la pandemia del coronavirus en estudiantes de la Universidad Antonio Nariño de la facultad de psicología sede Ibagué (2021)
The coronavirus pandemic has spread rapidly in Colombia. The objective of this study was to design an intervention in order to mitigate the emotional and psychological impact caused by the coronavirus pandemic in students of Antonio Nariño University from the psychology faculty in Ibague. The SCL-90-R Symptom Inventory was used as a measuring instrument. Adjusting it to google form, in such a way that it was accessible to the student population. The results indicated that UAN students have a high tendency to somatize and this somatization manifests with symptoms such as headache, back pain and little interest in daily work.